Anxiety and Depression in Bidirectional Relations Between Pain and Smoking: Implications for Smoking Cessation. (January 2016) - Zale, Emily L.; Maisto, Stephen A.; Ditre, Joseph W.
Pain and tobacco smoking are highly prevalent and comorbid conditions that impose considerable burdens on individuals and health care systems. A recently proposed reciprocal model suggests that these conditions interact in a bidirectional manner, resulting in greater pain and the maintenance of tobacco addiction. Anxiety and depression are common among smokers in pain and have been identified as central mechanisms of interest. There is emerging evidence that smokers with anxiety/depression may experience more severe pain and functional impairment, greater pain-induced motivation to smoke, and increased sensitivity to pain during periods of smoking abstinence. Based on empirical findings, we hypothesize that these experiences may engender expectations that abstaining from smoking will exacerbate both pain and negative affect, thus eroding self-efficacy for smoking cessation and increasing perceived barriers to quitting. The goal of this narrative review is to examine the role of anxiety/depression in complex pain–smoking relations so as to advance evolving theoretical perspectives and inform the development of tailored interventions.